Kualitas Pelayanan dan Fasilitas serta Pengaruhnya terhadap Kepuasan Konsumen pada M2M Indonesian Fast Food Cabang Pahlawan Mojokerto - Imam Wahyudi (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2021)
The purpose of this study was to analyze the simultaneous, partial and dominant effect of the variable quality of service and facilities on consumer satisfaction. This research is explanatory (explaining) is